(3GdahGFO GdLGeYI deYGfi GdNdGUI GdfGaYI aj YbGFO GdeYJRdIs - (3LeGd GdOjf Ydj Hf YHO Gddg Hf CMeO Hf CHi GdNjQs; (3CHh GdMSf CMeO Hf GdMSjf Hf eMeO Hf CHj HcQ GdQUGU GdUfYGfjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf EPG CQOfG GdcdGe Ydi eG PcQ GdTjN CMeO Hf GdMSjf GdQUGU ai cJGH GdNdGUI JcdefG ai SJI ehGVY s
(3BNQgG (B:s
(3hCeG GdehVY GdKGdK aceG PcQ GdTjN QMeg Gddg JYGdi , EdG Cf GdCeI ENJdaJ ai Gdfbd hGddg CYde JeJ GdahGFO GdLGeYI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B((3Yde GdcdGe (B84) s
Keywords: (3GdJhMjO hGdedd hGdfMds